Vouloir demeurer sans enfant: recension critique des écrits - Morrissette, Hélène; Spain, Armelle (Canadian Journal of Counselling and Psychotherapy, 2011)
This article summarizes and criticizes the research literature on voluntary childlessness in couples, then specifies the intention for a woman to remain childless. The various Stuo1Ies, mostly in sociology and psychology, identify the following factors about voluntary childlessness: incidence and trends, motives for and correlates of, differences with parents, decision and reaction of society to this phenomenon. The authors point out the evaluative and judgmental biases of these studies and suggest instead a descriptive and understanding approach to analyze the intention for a woman to remain childless.